Intensive care nurses' and nurse anaesthetists' motivation to enrol in an academic master's program: A qualitative study - Astrid Danielsen; Britt Sætre Hansen (Cappelen Damm Akademisk NOASP, 2024)
Background: Nurses worldwide are increasingly working in environments characterized by healthcare reforms, complex patient care and technological advancements that require the integration of evidence-based practice. There is also a growing need for continuous education, systematic competence research and competence assessment instruments to meet the rapid changes in critical and anaesthesia care settings. Aim: The aim of this study was to explore and describe anaesthetists' (NAs) and intensive care nurses' (ICNs) motivation for enrolling in an academic master's program. Method: A qualitative study was carried out, using focus groups. Data were analysed by means of qualitative content analyses. The participants were 11 students from an academic master's program at a Norwegian university. Findings: The participants' motivation was linked to the theme "improving patient care through continuous learning" and supported by three categories: understanding research; learning to argue within an intraprofessional team; improving and further developing the NAs and ICNs professions. Conclusion: Continuous learning to improve patient care for the critically ill was the main motivating factor for NAs and ICNs to enrol in an academic master's program. NAs and ICNs enrolled in the academic master's program with little or no support from the hospitals, and they reported that, in a busy ward, the time available for learning is scarce. The finding that NAs and ICNs desire continuous learning is relevant for hospital leaders who struggle to achieve patient safety goals and retain/recruit highly competent advanced nurses.